Clypeococcum cetrariae (Dacampiaceae, Ascomycota) in the Ukrainian Carpathians - Pirogov, M.V. (Український ботанічний журнал, 2015)
Clypeococcum cetrariae Hafellner is a new species for biota of Ukraine. The specimens of Cetraria islandica (L.) Ach.
infected by this fungus were collected in the Chornohora Mts. (Eastern Carpathians, Ukraine). Clypeococcum cetrariae
is a little known species of lichenicolous fungi in the world, therefore in the paper a description of this species and figures
are given. A key to Clypeococcum D. Hawksw. species is also provided Clypeococcum cetrariae Hafellner — новий вид для біоти України. Гербарні зразки лишайника Cetraria islandica (L.) Ach., інфіковані грибом, зібрані на території хребта Чорногора (Східні Карпати, Україна). Clypeococcum cetrariae є маловідомим видом ліхенофільних грибів у світовій біоті, тому в статті подано його опис, матеріал ілюстрований оригінальними фотографіями. Також наведено ключ для визначення видів роду Clypeococcum D. Hawksw. Clypeococcum cetrariae Hafellner — новый вид для биоты Украины. Гербарные образцы лишайника Cetraria islandica (L.) Ach., инфицированные грибом, собраны на территории хребта Черногора (Восточные Карпаты, Украина). Clypeococcum cetrariae является малоизвестным видом лихенофильных грибов в мировой биоте и поэтому в статье дано его описание, материал иллюстрирован оригинальными фотографиями. Также приведен ключ для определения видов рода Clypeococcum D. Hawksw.